2014
DOI: 10.1007/s10815-014-0259-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitrification versus slow freezing of human day 3 embryos on β-hCG levels

Abstract: Purpose The study was designed to investigate the effect of vitrification and slow freezing for the cryopreservation of human day 3 embryos on serum β-hCG levels in pregnancies established after frozen embryo transfer (FET). Methods Of the 1384 FET cycles initiated, 1131 embryo transfers met study criteria and assigned to one of two groups: 797 slow-freezing embryo transfers or 334 vitrified embryo transfers. Median values of β-hCG and outcome of all pregnancies were compared between the two groups. Predictive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Several studies have shown similar pregnancy and implantation rates between slow freezing and vitrification [13,27]. Vitrified embryo transfer is associated with lower hCG concentrations on day 12 post-embryo transfer compared with slow freezing embryo transfer [18]. In the current study, a higher implantation rate in slow freezing than in vitrification was found.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Several studies have shown similar pregnancy and implantation rates between slow freezing and vitrification [13,27]. Vitrified embryo transfer is associated with lower hCG concentrations on day 12 post-embryo transfer compared with slow freezing embryo transfer [18]. In the current study, a higher implantation rate in slow freezing than in vitrification was found.…”
Section: Discussionsupporting
confidence: 69%
“…Slow freezing of day 3 embryos was performed as described by Edgar et al [17], which involved a slow controlled freezing and thawing protocol with propanediol/sucrose (Freezing Kit; Irvine Scientific, Santa Ana, CA, USA) as the cryoprotectant, as described previously [18]. For vitrification of embryos, an open system was selected based on previous studies for its safety [19,20].…”
Section: Cryopreservation Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ovarian stimulation and IVF procedures have been previously described (Xue et al 2014;Xue et al 2018). Briefly, embryo culture with sequential media was carried out as follows: fertilization was performed in fertilization medium (G-IVF, Vitrolife Sweden AB, Sweden) containing 10% serum substitute supplement (SSS, Irvine Scientific, Santa Ana, CA).…”
Section: Ivf Proceduresmentioning
confidence: 99%
“…The following morning, the oocytes were individually placed in microdrops in cleavage medium (G-1, Vitrolife Sweden AB, Sweden) with 12 % SSS and incubated in incubators at 37℃ with 6 % CO 2 , 5% O 2 and 89% N 2 for 48 h before being frozen. Morphological assessment of embryos was based on the number of blastomeres and the proportion of cytoplasmic fragments and the uniformity of blastomeres (Xue et al 2014).…”
Section: Ivf Proceduresmentioning
confidence: 99%